2009
DOI: 10.1016/j.ydbio.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the ubiquitin ligase substrate adaptor MEL-26 are inversely correlated with MEI-1/katanin microtubule-severing activity during both meiosis and mitosis

Abstract: The MEI-1/MEI-2 microtubule-severing complex, katanin, is required for oocyte meiotic spindle formation and function in C. elegans, but the microtubule-severing activity must be quickly downregulated so that it does not interfere with formation of the first mitotic spindle. Post-meiotic MEI-1 inactivation is accomplished by two parallel protein degradation pathways, one of which requires MEL-26, the substrate-specific adaptor that recruits MEI-1 to a CUL-3 based ubiquitin ligase. Here we address the question o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…Consistently, reducing MEI-1 levels by inducing its premature degradation during meiosis, in egg-3(RNAi) embryos (Johnson et al, 2009) or reducing its activity [as is probably the case for the MEI-1 P99L/P235S variant (McNally and McNally, 2011)], does not prevent meiotic spindle assembly but rather leads to the assembly of a long meiotic spindle. Conversely, high MT-severing activity during meiosis, as observed in mei-1(ct46) embryos expressing the non-degradable MEI-1 P99L form, leads to the formation of a short meiotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, reducing MEI-1 levels by inducing its premature degradation during meiosis, in egg-3(RNAi) embryos (Johnson et al, 2009) or reducing its activity [as is probably the case for the MEI-1 P99L/P235S variant (McNally and McNally, 2011)], does not prevent meiotic spindle assembly but rather leads to the assembly of a long meiotic spindle. Conversely, high MT-severing activity during meiosis, as observed in mei-1(ct46) embryos expressing the non-degradable MEI-1 P99L form, leads to the formation of a short meiotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans, it was further reported that MEL-26 is induced during meiosis and that the protein is present only at low levels until the completion of meiosis, after which protein levels increase substantially (Johnson et al, 2009). It was shown that the level of MEL-26 itself is kept low during meiosis by the action of a CUL2-containing E3 ubiquitin ligase until it is required for the postmeiotic degradation of MEI-1.…”
Section: Discussionmentioning
confidence: 99%
“…MAB1 is additionally able to interact with At KTN1 (Arabidopsis p60 subunit of katanin). Specificity of the development and able to contribute to further mitotic divisions (Luke-Glaser et al, 2007;Johnson et al, 2009). The observation that MAB1 and CUL3a do not interact in the nucleus of tobacco BY-2 cells further suggests that unknown nuclear substrates may be degraded in the cytoplasm and are protected in the nucleus or that MAB1 may posses a CUL3a-independent function in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Since meiotic and mitotic spindles are assembled in the same cytoplasm, it is a challenge to achieve rapid inactivation of the MEI-1/MEI-2 complex after fertilization without attenuating its activity during the second division of meiosis. C. elegans solves this problem by subjecting the MEI-1 subunit to multiple levels of regulation, including ubiquitin proteolysis (23, 42, 4551). …”
Section: Timely Degradation Of Mei-1 By a Network Of Protein Degradatmentioning
confidence: 99%
“…4A) (50). The levels of MEL-26 protein are kept low in the oocyte by the action of an unknown CUL-2 based E3 ligase, although it is not known if this interaction is direct (45). Equally unclear is the mechanism of keeping CUL-3 MEL-26 turned off during meiosis, but one candidate for the switch is RFL-1 which activates E3 ligases by neddylation.…”
Section: Timely Degradation Of Mei-1 By a Network Of Protein Degradatmentioning
confidence: 99%